PENINGKATAN MINAT DAN HASIL BELAJAR SEJARAH MELALUI PENDEKATAN KONSTRUTIVISME MATERI PROSES INTERAKSI INDONESIA JEPANG DAN DAMPAK PENDUDUKAN JEPANG DI INDONESIAPADA SISWA KELAS XI IPS SMA NEGERI AJIBARANG SEMESTER 2 TAHUN 2010/2011 - Parsini, Parsini (MIIPS, 2010)
The research was conducted with the aim to determine the extent to which theeffectiveness and efficiency of constructivist approach in teaching history so as to increasestudent interest and learning outcomes for the subjects of history at the State High Schoolstudents Ajibarang. The research was conducted at State High School students Ajibarangclass XI IS 2 semesters 2 years 2010/2011 which lasted from February to July 2011. Thematerial is a process of interaction of Indonesia-Japan and Japans military occupation of the impact on peoples lives in Indonesia The method used in the research is experimental research. In this class action study, researchers used data sources that come from students who are often known as primary sources. Source data are drawn from the results of daily tests both the initial conditions of students, and data from the pretest. To interest students either obtained from observations made by teachers who do research as well as peers. For the initial condition data in the form of the learning outcomes of students with the material of the national movement in the eyes of students to obtain an average value of 55.There are several ways to collect data in this study, documentation, observation, orobservation and tests. Based on the techniques used in data collection techniques berupandocumentation, observation, questionnaires, and test the tools used in data collection include documents, items about the pre test and post test cycles I, II cycles and cycle III.Penelitian This class action using validation To browse the data by observation, the results of tests and questionnaires were analyzed first by calculating the number and the percentage is, and then interpreted in the form of exposure. From the data during the study than from the initial conditions until the third cycle there is an increasing though still below the average 5.5 KKM with the initial condition, 6.1 in Cycle I, Cycle II at 6.0 and 6.7 in Cycle III. This is probably because the material is too many and difficult. From this fact it is necessary to do research on the class action method or the other time with a different learning model